Evaluation of the tolerance and forage quality of different ecotypes of seashore paspalum - Jiang, Kai; Yang, Zhimin; Sun, Juan; Liu, Huancheng; Chen, Shenmiao; Zhao, Yongzhuo; Xiong, Wangdan; Lu, Wenjie; Wang, Zeng-Yu; Wu, Xueli (Frontiers in Plant Science, 2022)
Seashore paspalum is a halophytic warm season grass with wide applications. It is noted for its superior ability of salt tolerance in saline environments, but the nutritive value of Seashore paspalum and the influences of salinity has not been determined. Therefore, this research evaluated the relationship between agronomic traits and forage quality and identified the effects of short-term high-salt stress (1 week, 700 mM) on the growth and forage nutritive value of 16 Seashore paspalum ecotypes. Then assessment of seashore paspalum ecotypes for salt and cold tolerance based on survival rate of long-term high-salt stress (7 weeks, 700 mM) and natural low-temperature treatments were investigated. There were significant genetic (ecotypes) effects on plants heights, leaf-stem ratio, and survival rate of salt or low temperature of Seashore paspalum. Plants height was significantly and negatively correlated with leaf-stem ratio. But heights and leaf-stem ratio had no significant correlation with fresh weight and dry weight. High salinity decreased shoot fresh weight and dry weight (DW) respectively by 50.6% and 23.6% on average. Seashore paspalum exhibited outstanding salt tolerance and forage quality at high salinity. The survival rate of Seashore paspalum ecotypes varied from 6.5% to 49.0% under 700 mM NaCl condition for 7 weeks. The crude protein contents (CP) were 17.4% DW and 19.3% DW respectively on average at control and 700 mM NaCl condition that were not significantly influenced by ecotypes and high salinity. The average ether extract (EE) content ranged from 4.6% DW under control condition to 4.4% DW under salt condition that had not significant difference. The neutral detergent fiber (NDF) and acid detergent fiber (ADF) content of Seashore paspalum were 57.4% and 29.8% DW on average under control condition. Salt stress slightly reduced the NDF and ADF content (50.2% and 25.9% DW on average, respectively). Overall, Salt stress has not significant effect on the CP and EE content of most ecotypes, but slightly reduced the NDF and ADF content and improved relative feed value. The results supported Seashore paspalum as a good candidate for improving the forage on saline soils and could provide useful guidelines for livestock producers.